Motivational interviewing for screening and feedback and encouraging lifestyle changes to reduce relative weight in 4-8 year old children: design of the MInT study - Taylor Barry J; Rose Elaine A; Cox Adell; Haszard Jill; Dawson Anna M; Brown Deirdre; Taylor Rachael W; Meredith-Jones Kim; Treacy Lee; Ross Jim; William Sheila M (BMC, 2010)
Abstract Background Because parental recognition of overweight in young children is poor, we need to determine how best to inform parents that their child is overweight in a way that enhances their acceptance and supports motivation for positive change. This study will assess 1) whether weight feedback delivered using motivational interviewing increases parental acceptance of their child's weight status and enhances motivation for behaviour change, and 2) whether a family-based individualised lifestyle intervention, delivered primarily by a MInT mentor with limited support from "expert" consultants in psychology, nutrition and physical activity, can improve weight outcomes after 12 and 24 months in young overweight children, compared with usual care. Methods/Design 1500 children aged 4-8 years will be screened for overweight (height, weight, waist, blood pressure, body composition). Parents will complete questionnaires on feeding practices, physical activity, diet, parenting, motivation for healthy lifestyles, and demographics. Parents of children classified as overweight (BMI ≥ CDC 85th) will receive feedback about the results using Motivational interviewing or Usual care. Parental responses to feedback will be assessed two weeks later and participants will be invited into the intervention. Additional baseline measurements (accelerometry, diet, quality of life, child behaviour) will be collected and families will be randomised to Tailored package or Usual care. Parents in the Usual care condition will meet once with an advisor who will offer general advice regarding healthy eating and activity. Parents in the Tailored package condition will attend a single session with an "expert team" (MInT mentor, dietitian, physical activity advisor, clinical psychologist) to identify current challenges for the family, develop tailored goals for change, and plan behavioural strategies that best suit each family. The mentor will continue to provide support to the family via telephone and in-person consultations, decreasing in frequency over the two-year intervention. Outcome measures will be obtained at baseline, 12 and 24 months. Discussion This trial offers a unique opportunity to identify effective ways of providing feedback to parents about their child's weight status and to assess the efficacy of a supportive, individualised early intervention to improve weight outcomes in young children. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12609000749202